2016
DOI: 10.1111/1751-2980.12325
|View full text |Cite
|
Sign up to set email alerts
|

A non‐invasive magnetic resonance imaging‐based model predicts portal venous pressure

Abstract: The MRI-based formula has great potential for detecting portal hypertension. As a non-invasive measurement, it may be clinically accepted for the replacement of invasive modalities after further refinement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 36 publications
2
6
0
Order By: Relevance
“…SV, PVD and PVCSA are regarded as important indicators of portal hypertension . As expected, our study showed larger SV, PVD and PVCSA in patients with cirrhosis than healthy controls.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…SV, PVD and PVCSA are regarded as important indicators of portal hypertension . As expected, our study showed larger SV, PVD and PVCSA in patients with cirrhosis than healthy controls.…”
Section: Discussionsupporting
confidence: 88%
“…SV, PVD and PVCSA are regarded as important indicators of portal hypertension. 28 As expected, our study showed larger SV, PVD and PVCSA in patients with cirrhosis than healthy controls. Compared with TLV, SV normalized by BW, BSA and BMI seemed to be more useful for evaluating liver function and predicting complications in the cirrhotic group.…”
Section: Discussionsupporting
confidence: 88%
“…PVD is regarded as an essential indicator of portal hypertension[35]. However, there are limited studies assessing PVCSA, as it is difficult to measure.…”
Section: Discussionmentioning
confidence: 99%
“…In cirrhotic patients, due to the presence of portal hypertension and increased blood flow, the PVD, SVD and PVCSA values increase. A PVD > 13 mm is an important index to predict portal hypertension [31] . The mean PVD, SVD and PVCSA values in normal Chinese subjects in this study were 8.84 ± 1.55 mm, 5.53 ± 1.28 mm, 98.33 ± 33.08 mm 3 , respectively.…”
Section: Discussionmentioning
confidence: 99%